Effects of Texture and Discharge Products on the Discharge Performance of Mg Anodes for Mg Air Batteries. Issue 13 (1st October 2020) - Yang, Huabao; Bin Lei,; Wu, Liang; Jiang, Bin; Liu, Wenjun; Yang, Qin; Song, Jiangfeng; Huang, Guangsheng; Zhang, Dingfei; Pan, Fusheng
Abstract : Here, four representative Mg-3Al-1Zn (AZ31) anodes with different texture characteristics, i.e., ET0°, ET30°, ET60°, and ET90°, are assembled as the anodes for Mg-air batteries. The correlation between texture and discharge products and the influences of texture and discharge products on the discharge performance are studied. The results show that the discharge performance of the four anodes follows the order: ET90° > ET60° > ET30° > ET0°. The improved discharge performance is related to the two aspects: (i) the discharge activities of the (11-20)/(10-10) orientated grains are higher than those of the (0002) orientated grains, (ii) the discharge products formed on the (11-20)/(10-10) surface are more easily to fall off than those formed on the (0002) surface.